Obesity modifies prostatic specific antigen in men over 45 years - López Fontana, Constanza Matilde (2011)
OBJECTIVES: To determine whether lower serum prostate-specific antigen (PSA) concentration in obese men is caused by plasma hemodilution and/or decreased serum testosterone levels. METHODS: A sample of 413 men, from 45 to 75 years old, were randomly selected for the study among those who participated in prostate cancer screening at 2 urban urology practices in Argentina and Puerto Rico. Weight, height, serum testosterone and total PSA concentration were determined. Body mass index (BMI), body surface, plasma volume, and PSA mass were calculated. Prostate volume was estimated by transrectal ultrasound using the prolate ellipsoid formula. RESULTS: Mean age was 59 years old (range, 45 to 75) and mean BMI was 28.8 kg/m2 (range, 24 to 46). Mean serum PSA concentration was 1.43 ng/ ml in normal weight patients (n=68), 1.4 ng/ml in overweight patients (n=222), 1.05 ng/ml in obese patients (n=114), and 0.85 ng/ml in morbidly obese patients (n=9). BMI was directly correlated with plasma volume (r= 0.687; p= 0.001) and inversely correlated with serum PSA concentration (r= -0.235; P= 0.001). PSA mass tended to be lower in obese and morbidly obese patients (P= 0.0063) compared to normal weight and overweight subjects. Serum testosterone concentration (P= 0.91) and prostate volume (P= 0.068) were similar among all BMI groups. CONCLUSIONS: Obese men had lower serum PSA concentrations than normal weight men mainly due to plasma hemodilution. PSA mass tended to be lower in obese patients, but it is unlikely a consequence of lower serum testosterone concentrations.